Shear wave elastography for treatment monitoring of plantar fasciitis - Gatz, Matthias; Betsch, Marcel; Quack, Valentin; Bejder, Ljudmila; Schrading, Simone; Tingart, Markus; Dirrichs, Timm (Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROU ND: Plantar fasciitis is a common cause of heel pain. Monitoring therapy effects is challenging with conventional B-mode ultrasound. Shear wave elastography (SWE) provides important diagnostic information beyond B-mode, with typically lower tissue stiffness in symptomatic plantar fascia. Up to now little is known about SWE features for therapy monitoring in plantar fasciitis. We evaluated the clinical effects of a 3-month physical therapy based treatment and its influence on B-mode and SWE ultrasound findings in patients suffering from plantar fasciitis, correlating ultrasound findings to score-based symptom development. METHOD S: Prospective, IR B-approved clinical study in plantar fasciitis patients undergoing a 3-month physical therapy based treatment. Measurement time points were before (T0), after 1 (T1) and 3 (T2) months of treatment, consisting of clinical orthopedic (FFI , AOFA AOFAS-Score) and multimodal radiologic sonographic examinations (B-mode/SWE) using a high-resolution linear 18-MHz probe. RESULTS: A total of 33 patients with 43 symptomatic plantar fascia were included. We found a significant (P<0.001) clinical score improvement (AOFA AOFAS +14, FFI-Pain-21, FFI-Function-18) between T0 and T2. Mean initial thickness (T0) of symptomatic plantar fascia was 4.2 (±1.2) mm, compared to 3.2 (±0.7) mm at the asymptomatic contralateral side (P<0.001). No significant thickness changes were seen at T1 (4.2±1.1 mm) and T2 (4.5±1.3 mm), even though clinical scores improved significantly. Mean initial stiffness (T0) of symptomatic plantar fascia was 59.57 (±43.3) kPa, compared to 83.23 (±47.3) kPa at the asymptomatic contralateral side (P<0.001). In contrast to B-mode ultrasound, SWE values increased significantly between T0 (59.6±43.3 kPa), T1 (82.6±47.3 kPa) and T2 (102.5±47.2 kPa) (P<0.001-0.009), with positive correlations for AOFAS/FFI-Pain/Function scores (r=0.285-0.473, P<0.001-0.002). CO NCLU SIO NS: A physical therapy based treatment relieves plantar fasciitis symptoms during a 3-month period. In line with symptom reduction, stiffness (Young's-moduli) of plantar fascia increased significantly, while B-mode ultrasound revealed no measurable changes during the healing process. Shear wave elastography was able to quantify plantar fascia pathologies and their recovery under therapy.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Fasciitis; Neuromuscular Monitoring; Plantar; Ultrasonography